Time-varying interlinkages between digitalization, globalization, and carbon emission in Vietnam - Pham Hong Chuong; To Trung Thanh; Le Thanh Ha (Humanities & Social Sciences Communications)
Abstract Increasing economic integration in the globalization era has facilitated digitalization around the world. This paper examines the interlinkages between digitalization and internet infrastructure, economic openness, and CO2 emission in Vietnam from 1996 to 2022 using time-varying parameter vector autoregression (TVP-VAR). We use the extended joint interconnectedness approach to study the variation of five variables. Our results indicate that the Internet outbreak significantly determined the system-wide dynamic connectedness, especially between 1999 and 2006. Meanwhile, trade openness continuously serves as the net shock receiver of the system, but it fluctuated significantly before 2006. The role of mobile cellular subscription, FDI, and CO2 is interchangeable between shock transmitter and shock receiver, depending on considered periods. Pairwise directional connectedness zooms into how one variable transmits to or receives shocks from the other. Internet users extensively transmit shocks to FDI and mobile cellular subscriptions, but they receive shocks from CO2 from 2001 onward.